Wittgenstein in Translation : - Gorlée, Dinda L. (De Gruyter Mouton, 2012)
Apart from the Tractatus, Wittgenstein did not write whole manuscripts, but composed short fragments. The current volume reveals the depths of Wittgenstein's soul-searching writings - his
10.1515/9781614511137
Keywords: Intertextuality.; Semiotics and literature.; Translating and interpreting; Semiotik.; Übersetzungstheorie.; Wittgenstein.